Impact of Chronic Kidney Disease Under Nephrology Care on Outcomes of Carotid Endarterectomy. (May 2021) - Jeong, Min-Jae; Byun, Eunae; Chang, Jai W.; Kwon, Sun U.; Kim, Nayoung; Choi, Eol; Han, Youngjin; Kwon, Tae-Won; Cho, Yong-Pil
Abstract : Objective: This study aimed to investigate the impact of chronic kidney disease (CKD) and the delivery of nephrology care on outcomes of carotid endarterectomy (CEA). Methods: This was a single centre, retrospective observational study. Between January 2007 and December 2014, 675 CEAs performed on 613 patients were stratified by pre-operative estimated glomerular filtration rate (eGFR) values (CKD [eGFR < 60 mL/min/1.73m 2 ] and non-CKD [eGFR ≥ 60 mL/min/1.73m 2 ] groups) for retrospective analysis. The study outcomes included the occurrence of major adverse cardiovascular events (MACEs), defined as fatal or non-fatal stroke, myocardial infarction, or all cause mortality, during the peri-operative period and within four years after CEA. Results: The CKD group consisted of 112 CEAs (16.6%), and the non-CKD group consisted of 563 CEAs (83.4%). The MACE incidence was higher among patients with CKD compared with non-CKD patients during the peri-operative period (4.5% vs. 1.8%; p = .086) and within four years after CEA (17.9% vs. 11.5%; p = .066), with a non-statistically significant trend. In a subgroup analysis of patients with CKD under nephrology care (63/112, 56.3%; with better controlled risk factors and tighter medical surveillance by a nephrologist), patients with CKD without nephrology care (49/112, 43.8%), and non-CKD patients, the risk of both peri-operative (4.1% vs. 0.4%; p = .037) and four year post-operative (20.4% vs. 7.3%; p = .004) all cause mortality was statistically significantly higher among patients with CKD without nephrology care compared with non-CKD patients. However, there were no statistically significant differences between patients with CKD who received nephrology care and non-CKD patients in peri-operative and four year post-operative MACE occurrence, both in terms of the composite MACE outcome and the individual MACE components. Conclusion: Despite the higher risk of peri-operative and four year MACE after CEA among patients with CKD, and the statistically significantly higher peri-operative and four year post-operative all cause mortality rates among patients with CKD without nephrology care, patients with CKD under nephrology care had similar outcomes to non-CKD patients.